Families of Missing Children: Psychological Consequences and Promising Interventions in the United States, 1989-1991 - Hatcher, Chris ([Verlag nicht ermittelbar], 1997)
This study was conducted to examine the psychological reactions experienced by families of missing children and to evaluate families' utilization of and satisfaction with intervention services. To address issues of psychological consequences, the events occurring prior to child loss, during the experience of child loss, and after child recovery (if applicable) were studied from multiple perspectives within the family by interviewing parents, spouses, siblings, and, when possible, the missing child. A sample of 249 families with one or more missing children were followed with in-home interviews, in a time series measurement design. Three time periods were used: Time Series 1, within 45 days of disappearance, Time Series 2, at 4 months post-disappearance, and Time Series 3, at 8 months post-disappearance. Three groups of missing children and their families were studied: loss from alleged nonfamily abduction (stranger), loss by alleged family or parental abduction, and loss by alleged runaway. Cases were selected from four confidential sites in the United States. The files in this collection consist of data from detailed structured interviews (Parts 1-22) and selected quantitative nationally-normed measurement instruments (Parts 23-33). Structured interview items covered: (1) family of origin for parents of the missing child or children, (2) demographics of the current family with the missing child or children, (3) conditions in the family before the child's disappearance, (4) circumstances of the child's disappearance, (5) perception of the child's disappearance, (6) missing child search, (7) nonmissing child, concurrent family stress, (8) coping with the child's disappearance, (9) coping with a nonmissing child, concurrent family stress, (10) missing child recovery, if applicable, (11) recovered child reunification with family, if applicable, and (12) resource and assistance evaluation. With respect to intervention services, utilization of and satisfaction with these services were assessed in each of the following categories: law enforcement services, mental health services, missing child center services, within-family social support, and community social support. The quantitative instruments collected data on family members' stress levels and reactions to stress, using the Symptom Check List-90, Achenbach Child Behavior Check List, Family Inventory of Life Events, F-COPES, Frederick Trauma Reaction Index-Adult, and Frederick Trauma Reaction Index-Child.